Specific and non-specific effects of Mycobacterium bovis BCG vaccination in dairy calves - Contreras, Catalina; Alegría-Moran, Raúl; Duchens, Mario; Ábalos, Pedro; López, Renata; Retamal, Patricio (Frontiers in Veterinary Science, 2023)
Bovine tuberculosis (bTB) is a chronic disease mainly caused by Mycobacterium bovis, a zoonotic pathogen with economic significance as it leads to reduced milk and meat production, and high costs for control measures. The Bacillus Calmette-Guérin (BCG) vaccine, primarily used to prevent tuberculosis in humans, has also been studied for controlling bTB. While showing effectiveness in preventing M. bovis infection and disease in cattle, the BCG vaccine can induce non-specific effects on the immune system, enhancing responses to infections caused by unrelated pathogens, and also having non-specific effects on lactation. The aim of this study is to describe both the specific and non-specific effects of BCG vaccination in calves from a commercial dairy herd in central Chile. Diagnosis of M. bovis infection was performed through the IFN release assay (IGRA) using ESAT6/CFP-10 and Rv3615c antigens. The records of milk production, somatic cell count (SCC), clinical mastitis (CM) and retained placenta (RP) during the first lactation were compared between vaccinated and non-vaccinated animals. The breed (Holstein Friesian [HF] v/s HF x Swedish Red crossbred [HFSR]) and the season (warm v/s cold) were also analyzed as categorical explanatory variables. Results of IGRA showed significant differences between vaccinated and control groups, indicating a vaccine efficacy of 58.5% at 18 months post vaccination in HFSR crossbred animals. Although milk production did not vary, SCC and CM showed differences between groups, associated to the breed and the season, respectively. When analyzing CM and RP as a whole entity of disease, BCG showed protection in all but the cold season variables. Overall, the BCG vaccine induced protective specific and non-specific effects on health parameters, which may be influenced by the breed of animals and the season. These results provide new features of BCG protection, supporting initiatives for its implementation as a complementary tool in bTB control.